Suicide mortality, economics and subgroup segregation - Briggs, Thomas, author; Pena, Anita Alves, advisor; Bernasek, Alexandra, advisor; Zahran, Sammy, committee member; Canetto, Silvia, committee member (Colorado State University. Libraries, 2020)
In the United States, suicide is typically theorized as an individual act, and as symptom of a mental disorder. However, evidence shows that those who die of suicide (e.g., by sex, race) varies depending on cultural, social and economic factors. Research on the contexts of suicide has been marked by several limitations, including a tendency to analyze social and economic factors separately, and also a disregard for the combined role of sex and ethnicity in the relationship between social and economic factors and suicide. This study compares current statistics with past research and offers a different methodology in the estimation and model construction of the socioeconomic determinants of suicide. By examining the association between social and economic indicators and suicide among African descent men and women, as compared to European descent men and women in the United States, this study isolates the impact of business cycle fluctuations (as indicated by the unemployment rate) on socioeconomic flows in marital, educational and age groups. The first chapter compares previous research on suicide mortality conducted in Ruhm, (2000) over business cycles by exploiting socioeconomic data from 2005-2012. Using detailed suicide mortality data, I observe that previous trends in state level suicide determination via the unemployment rate, hold over this time period. My research also expands upon Ruhm (2000) by accounting for race and gender specific socioeconomic means and suicide rates, I determine that the strong correlation between the unemployment rate and the suicide rate, only holds for whites, in particular white males. The association is insignificant for every other demographic at the state level. I also estimated the association at the county level. In a comparison of the regions, county level aggregates found significance for each subgroup. A significant and negative association was found for blacks and significant and positive for whites. These results suggest that the detrimental effects of unemployment (alone) only affects whites, although the mechanism that increases suicide for blacks could be through other socioeconomic variables that are themselves impacted by the unemployment rate. The findings imply that the modeling technique used in previous research is not sufficient to obtain the appropriate results for every demographic subgroup or subregion. The second chapter studies the impact of socioeconomic status variables such as marital status, educational attainment, income level and inequality on the suicide count as well as regional controls on gun ownership and level of unemployment insurance. This section employs a zero-inflated negative binomial model, with modification for panel data. Results indicated that unemployment was significantly positive only for white males. Marriage has a significant and negative impact on every demographic subgroup with the exception of black females. The impact of inequality on black males and females was much more positive and significant by magnitude than that for white males and females. These findings suggest inequality as a significant factor on suicide during economic downturns, especially for blacks. Furthermore, these results suggest that business cycle fluctuations impact the black suicide rate through inequality thus, not through unemployment directly. The third chapter addresses economic frustration as a reason for the notable increase in suicide rates, particularly amongst poor whites. It is argued that the externalization of economic frustration by poor whites once led to homicide of blacks. Through changing social norms and penal consequences current economic and social frustration is internalized and leads to increased morbidity and suicide mortality in whites. I refer to the past perspective of one of the most influential black leaders, W.E.B. Dubois. I also provide a history of economic violence and analyze current phenomena using the philosophies of Dubois and add further evidence of the current state of affairs offered by Jonathan Metzl. Together these chapters suggest an alternative reasoning for increased suicide mortality in the U.S. As demonstrated, the current etiology does not universally account for the socioeconomic determinants of suicide mortality in the United States by subgroup or subregion. Furthermore, there has been s substantial disregard for the cultural changes in America that may account for rising suicide mortality in America, such as racial/ethnic saturation and the internalization of economic frustration in economic analysis.
Keywords: socioeconomic; suicide; stratification; business cycle